(untitled) (Journal of the College of Basic Education, 2026)
This study aims to investigate the impact of the Mind Mapping technique on the reading comprehension achievement of Iraqi EFL university students. The research was conducted during the 2025-2026 academic year at the University of Babylon, College of Basic Education. A sample of 70 second-year students was randomly selected and divided into two groups: an experimental group (n=35) taught via Mind Mapping and a control group (n=35) taught using the traditional method. The instrument employed was a researcher-designed reading comprehension post-test consisting of 40 items validated by a jury of experts. Data analysis using t-tests for independent samples revealed a significant statistical difference in favor of the experimental group, with a mean score of 13.89 compared to 0.99 for the control group (p < 0.05). The study concludes that Mind Mapping is a highly effective pedagogical tool for enhancing cognitive organization and information retrieval in reading.